2017
DOI: 10.17582/journal.aavs/2017/5.12.491.499
|View full text |Cite
|
Sign up to set email alerts
|

Practical Application of Guar (Cyamopsistetragonoloba L. Taub) Meal in Poultry Nutrition

Abstract: | Guar is a very important legume crop in arid areas of Indian sub-continent. Over the world, India is known as the biggest producer of guar bean by contributing around 90% of the total production. Guar meal is defined as a guar gum by-product which has about 450 gram protein per kilogram. In spite having high protein content, guar meal is not known on a commercial scale but it has received substantial attention for animal feedstuffs. Trypsin inhibitors are the main anti-nutritive factor present in guar; howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 42 publications
(63 reference statements)
3
13
0
Order By: Relevance
“…In contrast, Gutierrez et al (2007) reported that layers possess high production rate can get guar level up to 5% not more without negative effects on laying performance. On the other hand decreasing performance of egg production by increasing guar meal level up to 15% is in full agreement with Saeed et al (2017) who reported that 15% declined layer performance moreover Rao, et al (2015) reported that 15% can decrease EP, EM and AEW. In addition Hassan (2013) reported that feeding 20.0% guar meal lowered significantly EP% and EM of laying hens.…”
Section: Results and Discussion Production Performance Egg Productionsupporting
confidence: 86%
See 4 more Smart Citations
“…In contrast, Gutierrez et al (2007) reported that layers possess high production rate can get guar level up to 5% not more without negative effects on laying performance. On the other hand decreasing performance of egg production by increasing guar meal level up to 15% is in full agreement with Saeed et al (2017) who reported that 15% declined layer performance moreover Rao, et al (2015) reported that 15% can decrease EP, EM and AEW. In addition Hassan (2013) reported that feeding 20.0% guar meal lowered significantly EP% and EM of laying hens.…”
Section: Results and Discussion Production Performance Egg Productionsupporting
confidence: 86%
“…Diets with β-mannanase recorded significantly (P≤ 0.05) higher EP% and EM during different months and overall period than diets without β-mannanase. Desirable results of increasing guar meal level up to 10% on EP% and EM agree with Saeed et al (2017) who reported that 10% guar meal can supplement to diets with no harmful effects on poultry production performance. Furthermore guar meal can add to layer diets with higher rate of egg production such white leghorn up to 10% without harm effect on EP, EM and AEW (Rao, et al, 2015).…”
Section: Results and Discussion Production Performance Egg Productionsupporting
confidence: 72%
See 3 more Smart Citations